Clinical outcomes of allogeneic hematopoietic stem cell transplant with different stem cell sources in infant acute myeloid leukemia - Yuyang Wang; Yibing Guo; Xiuxin Ling; Junhui Li; Tao Hu; Zhaoxia Zhang; Mengze Hu; Zeliang Song; Mei Yue; Ruihong Tang; Dixiao Zhong; Rong Liu (Scientific Reports)
Abstract Acute Myeloid Leukemia (AML) in infants constitutes a rare and biologically distinct subgroup. Hematopoietic stem cell transplantation (HSCT) plays a pivotal role in the treatment of infant AML. However, the source of stem cells remains insufficiently explored. This study aimed to evaluate the clinical outcomes of allogeneic HSCT from different sources. We conducted a single-center retrospective analysis of 27 infants with AML who underwent HSCT. We compared peripheral blood (PB) with/without bone marrow (BM) (Group 1, n = 16) versus umbilical cord blood (UCB) (Group 2, n = 12). There was no significant difference in 3-year overall survival (OS), disease-free survival (DFS), 3-year recurrence rates, or one-year cumulative graft-versus-host disease (GVHD) incidence between two groups (3-year OS: 80.36% for group 1 vs. 91.67% for group 2, p = 0.5474; DFS: 73.66% vs. 69.84%, p = 0.8232; GVHD: 56.25% for group 1 vs. 50.0% for group 2, p = 0.824). The group with pre-transplant minimal residual disease (MRD) status had a lower recurrence rate. This study emphasizes the efficacy of HSCT in the treatment of infant AML, with higher OS rates compared to childhood AML. It also supports UCB as a viable stem cell source. Achieving MRD-negative status before transplantation is crucial for improving post-transplant outcomes.